Konsep Penataan Area Ruang Luar di Sekitar Candi Singosari, Kabupaten Malang, Jawa Timur - Lestari, Ni Kadek Ayu; Suryada, I Gusti Agung Bagus; Titisari, Ema Yunita; Paramadhyaksa, I Nyoman Widya (Jurnal Arsitektur Universitas Udayana, 2025)
Singosari Temple is one of Indonesia's cultural heritage sites that has historical value and beautiful architectural heritage. Observations show that Singosari Temple is the center of various activities, such as historical learning, archaeological research, and religious activities. To support the activities at Singosari Temple, a comfortable area or place for visitors is needed so that they feel comfortable when visiting. The arrangement of the outdoor space around the temple, including the landscape and vegetation, plays an important role in strengthening the aesthetic and spiritual value of the site. Therefore, it is important to conduct a study on the concept of the arrangement of the outdoor space area around Singosari Temple in order to provide an interesting new experience for tourists and increase the attractiveness of the Singosari Temple area. The researcher used qualitative methods through field observations, and interviews. This paper describes the concept of structuring the outdoor area around Singosari Temple that emphasizes the natural, cultural, and spiritual character of the temple to enhance the visitor experience and preserve the cultural values of Singosari Temple. The final results of the study show several innovative design concepts for the arrangement of outdoor spaces around Singosari Temple, such as the arrangement of environmentally friendly pedestrian paths, vegetation arrangements that strengthen cultural and spiritual values in response to the problems and potential contained therein. Keywords: candi singosari, outdoor space arrangement, landscape, vegetation